Maskulinisasi larva ikan nila (Oreochromis niloticus) melalui penggunaan madu dengan konsentrasi berbeda - Odara, Soesanti S; Watung, Juliaan Ch; Sinjal, Hengky J (Universitas Sam Ratulangi, 2015)
This study aimed to determine the effect of concentration of honey on masculinization of nile tilapia female. The study had four treatments, each with three replications. The experimental design used was completely randomized design (RAL). Data was analyse using Analysis Of Variance (ANOVA) followed by LSD at 5% and 1%. Broodstock was soaked in 1 L of water with treatment A 0 mL (without honey), B (5 mL honey), C (10 mL honey), D (15 mL honey) for 10 hours. After soaking, fish was reared in pan for one month. The percentage of male was determine by comparing the length and width of the red blood cells under a microscope. The results showed the the use of honey had significant effect on female masculinization. The percentage of male larvae tended to increase with the increase of honey dose. The highest percentage of male was obtained in treatment D (15 ml) that was 80%. Keywords: Honey, masculinization, larvae, Oreochromis niloticus